An exhaustive review of the metaheuristic algorithms for search and optimization taxonomy, applications, and open challenges - Rajwar, Kanchan (Artificial intelligence review, 2023)
© The Author(s), under exclusive licence to Springer Nature B.V. 2023, Springer Nature or its licensor (e.g. a society or other partner) holds exclusive rights to this article under a publishing agreement with the author(s) or other rightsholder(s); author self-archiving of the accepted manuscript version of this article is solely governed by the terms of such publishing agreement and applicable law.